PENGARUH DEFISIENSI FOLAT TERHADAP FERTILITAS INDUK DAN KUALITAS JANIN TIKUS - E.S., Moch. Istiadjid (Fakultas Kedokteran Universitas Brawijaya, 2004)
This experimental study was performed to reveals the association of folic acid deficiency with the rat’s fertility and also with life quality of baby’s rat. The level of folic acid deficiency were divided into two groups, consisted of severe and mild, based on the intake of folic acid, those were given to each groups that consist of ten mature Sprague-Dawley rats. Other were givennormal folic acid as a control. Sixteen weeks after dietary suplly, rat’s blood were evaluated to measure the contain of folic acid in the serum and erythrocyte and then the rats were forced mating. Baby rats were born with histerostomy. Rat’s fertility were evaluated by measured the number of delivered baby’s rat in 21th, 42th and 63th gestation or delivered days at each group. The quality of baby’s rats were evaluated by measured the body weight of each baby and examined of any kind of congenital anomaly, such as spina bifida, encephalocele or anencephaly. The data analysis suggested the positive impact of maternal folic acid level in erythrocyte and maternal serum with the level of maternal fertilityand life quality of the baby,s, especially its body weight. Thus, the deficiency of folic acid will cause maternal infertility, lowered body weight of the baby’s rats and may be also congenital anomaly. Key words:Folic acid deficiency, infertility, low body weight, congenital anomaly.